Analysis of sustainability reporting in the private sector and public sector: Scoping review approach - Winny Rohita Novyana; Agus Bandiyono (Indonesia Accounting Research Journal, 2025)
The Kyoto Protocol and the Paris Agreement emphasize accountability and reporting on activities carried out concerning efforts to reduce greenhouse gas (GHG) emissions and address climate change. Therefore, sustainability reports are needed to create transparency in mitigating and adapting to climate change. Sustainability reports have also evolved from focusing only on environmental aspects to being more holistic, considering ESG (Environmental, Social, and Governance) factors. This study uses the scoping review method to analyze how sustainability reporting is carried out in the private and public sectors. The study results show that sustainability reporting in both the private and public sectors aims to increase transparency and legitimacy through sustainability reporting. However, the two sectors' approach, focus, and triggers differ according to the regulatory context, organizational objectives, and stakeholder needs. This article is expected to contribute to providing literature that reviews the analysis of sustainability reporting in the private and public sectors, improves the quality of sustainability reporting in the private sector, and encourages sustainability reporting in the public sector.